Reluctant Representatives - Ganter, Elizabeth (ANU Press, 2016)
'How can you make decisions about Aboriginal people when you can't even talk to the people you've got here that are blackfellas?' So 'Sarah', a senior Aboriginal public servant, imagines a conversation with the Northern Territory Public Service. Her question suggests tensions for Aboriginal and Torres Strait Islanders who have accepted the long-standing invitation to join the ranks of the public service. Reluctant Representatives gives us a rare glimpse into the working world of the individuals behind the Indigenous public sector employment statistics. This empathetic exposé of the challenges of representative bureaucracy draws on interviews with Aboriginal and Torres Strait Islander Australians who have tried making it work. Through Ganter's engaging narration, we learn that the mere presence of Aboriginal and Torres Strait Islanders in the public service is not enough. If bureaucracies are to represent the communities they serve, Aboriginal and Torres Strait Islander public servants need to be heard and need to know their people are heard.